Systematic review and meta-analysis of molecular tumor board data on clinical effectiveness and evaluation gaps - Beryl Primrose Gladstone; Janina Beha; Arisa Hakariya; Pavlos Missios; Nisar P. Malek; Michael Bitzer (npj Precision Oncology)
Abstract Molecular Tumor Boards (MTBs) are pivotal in personalized cancer care. This systematic review and meta-analysis included 34 studies out of 576 articles (2020–January 2024) involving 12,176 patients across 26 major cancer entities. Of these, 20.8% (2,532 patients) received MTB-recommended therapies, with 178 outcome measures reported, achieving a median overall survival (OS) of 13.5 months, progression-free survival (PFS) of 4.5 months, and an objective response rate (ORR) of 5–57%. A pooled PFS2/PFS1 ratio ≥ 1.3 from 14 reports was observed in 38% (33–44%) of cases. Comparative data showed improved outcomes for MTB-treated patients, with hazard ratios of 0.46 (0.28–0.76, p < 0.001) for OS in 19 and 0.65 (0.52–0.80, p < 0.001) for PFS in 3 studies. These results highlight the benefits of MTB evaluations in improving outcomes for patients with solid tumors but also emphasize the need for standardized evaluation criteria to enable robust comparisons across studies.